Abelhas visitantes florais e potenciais polinzadores da macieira (Malus domestica Borkh.) no semiárido brasileiro - Monteiro, Victor Magalhães (2014)
This study aimed to investigated aspects of floral biology and possible limiting factors to pollination, investigate the use of bees, Apis mellifera, and the role of other insects visitors in apple pollination (Malus domestica Borkh.) in crops in the Brazilian northeast semiarid region. The study was conducted in an experimental area which has 0.5 hectare on FrutaCor® farm, Russas - Ceará. We used Two apple’s varieties in this study. The Julieta variety was used as pollen donor and the Princessa variety was used as receiving pollen. Theses varieties need chemical and physical treatment to flower break dormancy occurred. The study was conducted for 39 days at the end of October and early December 2013. Julieta Flowers lasted for fewer days than the princessa (VarJulieta = 2.04 ± 0.197, 2.93 ± 0.274 VarPrincesa; Mann-Whitney U = 150, p <0.0001). The pollen release of Julieta started at 09: 00h on the first day and had peaking at 13: 00h in the second day. The stigmatic receptivity of Princessa variety started during the stage "balloon" remaining until senescence. There was an average loss of Juliet’ anthers number of 19.87 ± 15.79% that effectively released pollen in relation to the total production per flower. The average of temperature 30,21ºC ± 4.18, may have been responsible for the reduction in longevity, loss of anthers and pollen loss, and is therefore recommended to increase the number of pollen donor plants in crops in semi-arid environments. The most abundant flower visitors were insects and among these, the bees representing approximately 61.86% of the total. Apple tree flowers had visitation peak in the morning, 5:00 to 12: 00h (81.57%). Therefore this culture is a cross-pollination-dependent to ripening of fruit, we observed the different ages flowers attractiveness by bees and we obtained 18.66 ± 4.93; 41.3 ± 7.63 and 4.6 ± 1.52, on 1 flowers, 2 and 3 days, respectively, showing that the 2nd day flowers are more attractive to bees (p <0.05). We observed that only a visit of Apis mellifera was enough to promote fruit set, regardless of the age of the flower. The introduction of this bee colonies in the orchard is necessary because A. mellifera was the most frequently observed species in apple tree flowers.